2018
DOI: 10.1002/cche.10045
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of some mineral nutrients and vitamins in advanced hulled wheat lines

Abstract: Background and objectives: Ancient wheat species, einkorn and emmer wheat, are potential healthy food sources for their vitamin and element contents. The aim of this study was to evaluate some elements and vitamin A and B complex of 36 einkorn and 49 emmer wheat advanced lines tested under field conditions. Findings: The results showed that some emmer wheat lines were extremely higher than those from einkorn and durum wheat checks for microelements. The mean concentrations of Fe, Zn, Cu, Mn, and Se of the emme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 33 publications
(58 reference statements)
0
14
0
Order By: Relevance
“…Özkan et al (2007) and Tekin et al. (2018) reported a positive correlation between Zn and Mn and Cu in the einkorn wheat population. Zhao et al.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Özkan et al (2007) and Tekin et al. (2018) reported a positive correlation between Zn and Mn and Cu in the einkorn wheat population. Zhao et al.…”
Section: Discussionmentioning
confidence: 94%
“…and Se which play a crucial role in human health and human growing (Kibar, 2019;Özkan et al, 2007;Tekin et al, 2018). Mineral 112.50 and 151.2 mg 100 g −1 , 46.9 and 47.1 mg 100 g −1 , and 3.5 and 8.5 mg 100 g −1 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Ancient wheats, mainly einkorn and emmer, are being increasingly considered due to their high levels of nutrients, elements, amino acids and phytochemicals. 1,2 These valuable plant materials have also been suggested for addition in the diet of patients suffering from some health problems such as elevated cholesterol, rheumatoid arthritis, some cancer types, high blood allergies, colitis and depression. 3 Therefore, it can be supposed that the ancient wheats and their products (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Suchowilska et al [ 16 ] reported concentrations of Fe, Zn, and Cu close to 49, 54, and 4.1 mg∙kg −1 , respectively, and highlighted significant positive correlations between Fe, Zn, and Mn levels in T. dicoccum grains. Similarly, the mean concentrations of Fe, Zn, and Cu in emmer wheat lines were 41.72 mg∙kg −1 , 17.06 mg∙kg −1 , and 2.85 mg∙kg −1 , respectively [ 15 ]. The concentrations of the microelements and TKW in the emmer wheat observed in this study agreed with the data reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, an ancient wheat variety, i.e., a tetraploid emmer wheat ( Triticum turgidum subsp. dicoccum ), is being increasingly recognized as a valuable food source for its high content of resistant starch, fiber, carotenoids, antioxidant compounds, and vitamins B2, B5, B6, and A [ 12 , 13 , 14 , 15 , 16 ]. Published reports have also indicated that wild and primitive wheats, such as T. monococcum , T. dicoccon , and T. dicoccoides , accumulate more Fe and Zn in grains than cultivated wheat and advanced lines [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%